E-Catalog Promotion of Fishermen Business Group with User Centered Design Method - Nasrullah, Muchamad Fajri Amirul; Yulius, Rina; Nizan, Muhamad Sahrul; Handayani, Siskha; Failasuf, Banu (Universitas Trilogi, 2024)
This research aims to design a promotional e-catalog for fishing business groups using the User Centered Design (UCD) method to improve the quality of their promotional services online. The partners in this research are the Fisheries Supervisory Community Group in Batu Basar Village, Nongsa District, Batam City, Riau Islands. So far, this group and fishermen have often faced obstacles in promoting their products effectively to potential consumers, especially in the rapidly developing digital era. The UCD method used in this research is a user-focused approach. The initial stage of research includes gathering information regarding the needs and preferences of potential users, including fishing business groups and potential consumers. This information was obtained through interviews, observations and literature studies. Based on the data collected, a promotional e-catalog was designed that took into account user needs and promotional objectives which included features such as complete product descriptions, product photos, price information, user testimonials and contact information. After the design is complete, the manufacturing stage is carried out and then continues to the testing stage involving potential users. This testing aims to maximize usability, efficiency and user satisfaction. The test results used the Nielsen model with five indicators with the results of Easy To Learn getting a score of 3.85, Efficiency To Use getting a score of 3.75, the Easy To Remember indicator getting a score of 3.85, and the Few Errors indicator getting a score of 4.05. Then the fun to use indicator has a value of 3.95.